The evolution of evidence-based practice guidelines in autism spectrum disorder: how can these begin to support individualized, community-based practices? - Doehring, P.; Reichow, B.; Volkmar, F.R. (Handbook of Evidence-Based Practices in Autism Spectrum Disorder, 2025)
Evidence-based practice guidelines use specific rubrics to first evaluate the quality of individual outcome research studies and then the overall strength of the evidence, ultimately generating recommendations for clinical and educational practice. This chapter reviews the methodologies used across three different types of guidelines spanning health and education, by comparing recommendations related to practices for addressing sleep problems. The review reveals that these guidelines share many features, with some differences suggesting areas of improvement. More fundamental differences between biomedical and psychosocial practices, as well as specific challenges of community-based practices, suggest other opportunities for improvement in the design of outcome research and in the development of practice guidelines. This chapter concludes by discussing how to close other gaps in guideline development by emphasizing focused practices instead of comprehensive treatment programs (CTPs), integrating research findings from related populations, developing recommendations for program and policy leaders, and imagining reviews that potentially offer more individualized recommendations. © Springer Nature Switzerland AG 2025.
Keywords: Autism spectrum disorder; Evidence-based practice; Outcome studies; Professional practice guidelines; Systematic research reviews; dept.sed